2007
DOI: 10.1002/path.2219
|View full text |Cite
|
Sign up to set email alerts
|

The heat‐shock protein 90 inhibitor, geldanamycin, induces apoptotic cell death in Epstein–Barr virus‐positive NK/T‐cell lymphoma by Akt down‐regulation

Abstract: NK/T-cell lymphoma (NKTL) is strongly associated with latent Epstein-Barr virus (EBV) infection. Recently, latent membrane protein 1 (LMP1), an EBV oncoprotein, was reported to activate the phosphatidylinositol-3 kinase (PI3K)/Akt pathway for cell survival. Because geldanamycin (GA) and its derivative, 17-allylamino-17-demethoxygeldanamycin (17-AAG), exhibit anti-tumour activity by degrading HSP90 client proteins, including Akt, we investigated the effect of GA and 17-AAG on the survival of NKTL cell lines. EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…The concentration of 17AAG used in this study was 10 M, which is relatively higher compared with those used in other studies (up to 2 M) (Jeon et al, 2007;Al Shaer et al, 2008;Meyer et al, 2008), although this is consistent with the relative resistance of HSCs to apoptotic stimuli (Novo et al, 2006;Hannivoort et al, 2008). We then attempted to sensitize HSCs to 17AAG-induced apoptosis.…”
Section: Resultssupporting
confidence: 78%
“…The concentration of 17AAG used in this study was 10 M, which is relatively higher compared with those used in other studies (up to 2 M) (Jeon et al, 2007;Al Shaer et al, 2008;Meyer et al, 2008), although this is consistent with the relative resistance of HSCs to apoptotic stimuli (Novo et al, 2006;Hannivoort et al, 2008). We then attempted to sensitize HSCs to 17AAG-induced apoptosis.…”
Section: Resultssupporting
confidence: 78%
“…Sun et al previously reported that Hsp90 inhibitors decreased expression of EBNA1 in EBV-infected cells, retarding the growth of EBV latently infected malignant cells via an EBNA1-dependent mechanism (43). Jeon et al described geldanamycin induction of apoptotic cell death in Epstein-Barr virus-positive NK/T-cell lymphoma cells by Akt downregulation (44). It is possible that inhibition of EBV DNA replication by the Hsp90 inhibitor may be due to effects not only on EBV DNA polymerase but also on other essential factors.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV oncoprotein LMP1 reportedly activates the phosphatidylinositol-3 kinase (PI3K)/Akt pathway to induce cell survival (Jeon, 2007). The intrinsic level of pAkt was higher in EBV-positive NK cells than in EBV-negative NK cells.…”
Section: Kinase Inhibitormentioning
confidence: 99%